Penegakan Hukum Bagi Pengguna Sepeda Listrik di Jalan Raya Dalam Perspektif Hukum Positif Indonesia (Undang-Undang Lalu Lintas) - Hermawati, Mutiara; Hanan Nuhi, Muhammad; Andari, Astriana; Marito, Eugina Evita; Farros, Naufal; Josua, Haezer; M, Mulyadi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The emergence of electric bicycles has become a special focus of the government as an effort to reduce the use of conventional gasoline-fueled vehicles in order to reduce the level of pollution due to gas emissions produced by these vehicles. Therefore, various laws and regulations have been issued to regulate electric bicycles, such as Law Number 22 of 2009 concerning Road Traffic and Transportation and Minister of Transportation Regulation No. 45 of 2020 concerning Certain Vehicles Using Electric Motor Drives. However, in reality, it is the users of electric bicycles who cause many cases of traffic violations due to misuse of electric bicycles as a result of the absence of strict sanctions stated in these two laws. The aim of this research is to explain the legal regulations for every electric bicycle user in Indonesia as well as what legal measures are used by the government to increase public compliance as electric bicycle users, especially on the highway. The research method used in this research is qualitative in the form of a case study with the data collection method for this research using the literature study method. The conclusion of this research is that as a result of the emergence of various traffic violations by electric bicycle users, regulatory updates are needed in an effort to provide clarity regarding the restrictions that must be met and the prohibitions that must be avoided by every electric bicycle user. The advice we give is to update the laws and regulations regarding restrictions and strict sanctions if electric bicycle users commit violations as an effort to enforce law in Indonesia.